Food choice, activity level, and carbon footprint: exploring potential for sustainable food consumption practices in young adults - Wollmar, Mari; Post, Anna; Sjöberg, Agneta (Frontiers in Nutrition, 2024)
This study aims to explore climate consciousness in relation to food consumption in young adults, examining its relationship with physical activity level and gender. A mixed-method approach is utilized, integrating seven-day food records and semi-structured interviews, employing social practice theory in our analytical framework. Our cohort of 47 participants (25 women, 22 men) displays varied diets, from omnivores to vegans. Moderately-active women show the lowest carbon footprint, favoring climate-conscious choices related to lower energy needs and plant-based preferences. Highly-active individuals consume more energy, resulting in a higher carbon footprint. Gender differences are evident, women were inclined to climate-conscious food practices motivated by animal ethics and health concerns. Conversely, men demonstrated a tendency for meat consumption. Participants share an understanding of carbon footprint, reflecting a solid awareness of food-related climate impact but differ in priorities; performance for highly-active, and economy for moderately-active. This highlights a mix of commonalities and distinctions, informing flexible, sustainable food practices. Higher activity levels are linked to greater energy needs and a higher carbon footprint. The highly-active group prioritizes performance in their food choices, while the moderately-active group focuses on economic considerations. Moderately-active women show the most climate-conscious food choices, leading to the lowest carbon footprint. Our findings indicate that highly-active individuals and men have significant potential to improve climate-adapted food consumption.